The Global Industrial Robot Trade Network: Evolution and China’s Rising International Competitiveness - Huijie Yang; Shaobin Wei; Haiyan Zhou; Feng Hu; Yufeng Chen; Hao Hu (Systems)
This paper examines the spatial and temporal evolution of the global industrial robot trade network (GIRTN) from 2000 to 2023 using complex network analysis, and it systematically evaluates China’s position in the GIRTN and its evolutionary trend by combining node reciprocity, the industry concentration index, the Herfindahl–Hirschman index, and betweenness centrality. The study shows that the GIRTN is characterized by significant imbalance, a “small world”, and weak reciprocity. Traditional industrial countries such as Japan, Germany, and France have dominated the global market for a long time, accounting for more than 80% of the market share. However, market imbalances have been mitigated with the rise of emerging economies such as China, South Korea, and Singapore. Despite increasing global trade linkages, there are significant differences in trade intensity. China’s position and competitiveness in the GIRTN have significantly improved, as demonstrated by its continued rise in the ranking of total exports, the improvement in the attractiveness and quality of its products, the diversification of its trading partners, and the optimization of its export structure. These changes indicate that China has gained significant competitive advantages and has great potential for development.